2022
DOI: 10.3390/ijerph19148709
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Survival of Patients Hospitalized with COVID-19 in Espírito Santo, Brazil

Abstract: Objective: To analyze the survival of patients hospitalized with COVID-19 and its associated factors. Methods: Retrospective study of survival analysis in individuals notified and hospitalized with COVID-19 in the state of Espírito Santo, Brazil. As data source, the reports of hospitalized patients in the period from 1 March 2020, to 31 July 2021 were used. The Cox regression analysis plus the proportional risk assessment (assumption) were used to compare hospitalization time until the occurrence of the event … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 42 publications
1
12
0
1
Order By: Relevance
“…Although there was a predominance of the sample among the lowest education levels of almost 30%, going in the same direction as other studies (11,25,26), there was no statistical difference in the length of hospital stay for these categories among the three waves. People from secondary and higher education, speci cally in the third wave, had this time increased, mainly among the higher education, whose average jumped from 10.5 days in the rst wave to 14 days in the third, re ecting slower progress and worsening of cases.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Although there was a predominance of the sample among the lowest education levels of almost 30%, going in the same direction as other studies (11,25,26), there was no statistical difference in the length of hospital stay for these categories among the three waves. People from secondary and higher education, speci cally in the third wave, had this time increased, mainly among the higher education, whose average jumped from 10.5 days in the rst wave to 14 days in the third, re ecting slower progress and worsening of cases.…”
Section: Discussionsupporting
confidence: 69%
“…Initially, approximately a quarter of people diagnosed with COVID-19 had developed serious conditions; of these, 80% needed to be admitted to the intensive care unit (ICU) (10). A recent study analyzing the survival of patients hospitalized with COVID-19 in the state of Espírito Santo, Brazil, found that the group of people aged 80 years or older who were smokers, obese, had chronic cardiovascular disease, chronic kidney disease, chronic neurological disease, and neoplasms were associated with a shorter survival time (11). Thus, it was possible to observe that some priority groups had more severe outcomes, such as death, owing to the favorable characteristics of these events.…”
Section: Introductionmentioning
confidence: 99%
“…No entanto, quanto à gravidade e mortalidade, estudos (PALAIODIMOS et al, 2020;GARBIN et al, 2022;GUIMARÃES et al, 2022) apontam maior frequência nas pessoas em idade avançada. Uma revisão sistemática realizada por Noor e Islam (2020), incluindo estudos entre janeiro e agosto de 2020 trouxe maior frequência de infecção Brazilian Journal of Development, Curitiba, v.9, n.1, p. 3747-3764, jan., 2023 naqueles com idade acima de 65 anos, do sexo masculino e apresentando comorbidades.…”
Section: Discussionunclassified
“…A recent study published, which aimed to analyze the survival of patients hospitalized with COVID-19 and its associated factors in Brazil, has concluded that non-work-related infection, age group above or equal to 60 years, presence of chronic cardiovascular disease, chronic kidney disease, chronic neurological disease, smoking, obesity, and neoplasms were associated with a higher risk of death, and, therefore, a lower survival in Brazilian patients hospitalized with COVID-19 [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The first study conducted in the state of Espírito Santo, Brazil which aimed to analyze the survival of patients hospitalized by COVID-19 with the source of data from the state’s official Health Surveillance Information System, have shown that the risk factors for death from COVID-19, such as the age group 60 to 79 years, and 80 years or more, non-work infection, patients with comorbidities, especially cardiovascular, chronic kidney disease, chronic neurological disease, smoking, obesity and neoplasms were associated with lower survival [ 9 ]. A cross-sectional study undertaken in Kazakhstan, identified 80% of cases of COVID-19 infection were asymptomatic or mild, and among the symptoms, the most common were cough (20.8%) and sore throat (17.1%), fever (11.6%) and runny nose (7.2%).…”
Section: Introductionmentioning
confidence: 99%